3x - 9y = 27-9y = -3x + 279y = 3x - 27y = x/3 - 3The graph is a straight line, with (slope = 3), and passing through the point (y = - 3) on the y-axis.
Get in function form. - 3X - Y = 4 - 1(- Y = 3X + 4) Y = - 3X - 4 ----------------------------solve for X and Y by the 0 out method - 3X - 4 = 0 - 3X = 4 X = - 4/3 --------------- Y = - 3(0) - 4 Y = - 4 -------------- Draw a line linking those points.
3x + y = c where c is any constant number of your choice.
Let's simplify: f(x) = 3x-3x, so f(x) =0, so y=0 The graph is a line along the x-axis.
3x+12 = 18 3x = 18-12 3x = 6 x = 2
3x-y=2 3x=y+2 y=3x-2 Some points: (0.-2)(1,1)(2.4)
3x + y = -4 -3x -3x y = - 4 -3x now plug in points!+++To clarify the principle, re-arrange the equation so it reads as "y = [something done to x]" then calculate a table of points for the plot itself.
1
The graph of [ y = -3x ] is a straight line, through the origin, with slope of -3 .
I don't understand your question but y=3x is the function of a graph, to graph the function you would plug points into the function such as x=0, x=1, x=-1 and you would find the y values at each point so that you can graph it. In this case the graph is a parabola which has a u shape.
-5
5
-7
Sensible but hard to explain
No pairs of points are given so the question cannot be understood
you put the y intercept at 2, the x intercept at -2/3 and you join those two points.
1